Association of epicardial adipose tissue thickness and inflammation parameters with CHA2DS2-VASc score in patients with nonvalvular atrial fibrillation - Akdag S; Simsek H; Sahin M; Akyol A; Duz R; Babat N (Dove Medical Press, 2015)
Serkan Akdag, Hakki Simsek, Musa Sahin, Aytac Akyol, Ramazan Duz, Naci Babat Department of Cardiology, Yuzuncu Yil University Medical Faculty, Van, Turkey Background: Epicardial adipose tissue (EAT), mean platelet volume (MPV), platelet-to- lymphocyte ratio (PLR), and neutrophil-to-lymphocyte ratio (NLR) have been shown to be helpful in predicting adverse cardiovascular events. However, to date, in the literature, there have been no studies demonstrating the relationship between EAT, MPV, PLR, NLR, and thromboembolism risk in atrial fibrillation (AF). Therefore, we examined the relationship between EAT, MPV, PLR, NLR, and CHA2DS2-VASc score used for the evaluation of thromboembolism risk in patients with AF.Methods: The study included 96 consecutive patients with AF and 52 age- and sex-matched control subjects. We calculated CHA2DS2-VASc risk score for each patient and measured baseline EAT thickness, MPV, PLR, NLR, left atrial volume index, and left ventricular ejection fraction.Results: The group with high CHA2DS2-VASc score had higher EAT (7.2±1.5 vs 5.9±1.2 mm, P<0.001), MPV (9.1±1.1 vs 8.4±1.0 fL, P=0.004), PLR (152.3±28.4 vs 126.7±25.4, P=0.001), and NLR (4.0±1.6 vs 3.2±1.3, P<0.001) compared to group with low-intermediate CHA2DS2-VASc score. Moreover, CHA2DS2-VASc score was found to be positively correlated with EAT (r=0.623, P<0.001), MPV (r=0.350, P=0.004), PLR (r=0.398, P=0.001), and NLR (r=0.518, P<0.001).Conclusion: Our study results demonstrated that EAT thickness, MPV, PLR, and NLR were associated with the thromboembolic risk exhibited by CHA2DS2-VASc score in patients with nonvalvular AF. Keywords: atrial fibrillation, epicardial adipose tissue, platelet, neutrophil, mean platelet volume